Occupational cancer and reproductive outcomes in the semiconductor industry: the need for an international epidemiologic study - Bailar III, John C; LaDou, Joseph (European Journal of Oncology and Environmental Health, 2009)
Occupational health of semiconductor workers has been the subject of only a few, limited investigations, all in developed countries. Findings of reproductive problems and increased risk of several cancers have not been adequately followed up by larger, more definitive studies. Industry and government have failed to take the initiative to protect workers before the industry was exported to many regions of the world. There is a compelling need for a large, international epidemiologic study of the semiconductor industry and its workforce.